(untitled) (Eurasian Journal of Research, Development and Innovation, 2025)
In the context of rapid socio-economic transformation, globalization, and the transition toward a knowledge-based society, the development of higher-order cognitive skills in students has become a central objective of modern education systems. Among these skills, investigative thinking occupies a particularly important position, as it enables learners to analyze complex problems, generate hypotheses, evaluate evidence, and construct reasoned conclusions in both academic and real-world contexts. Traditional instructional models, which often emphasize reproductive learning and linear knowledge transmission, have proven insufficient for cultivating such forms of thinking in contemporary learners. As a result, increasing attention has been directed toward innovative pedagogical paradigms that integrate cognitive, creative, and interdisciplinary dimensions of learning. This scientific article aims to explore the theoretical foundations of developing investigative thinking in students through an integrative-creative approach, which combines elements of integration across disciplines, creative problem-solving, and learner-centered instructional design. The study analyzes key philosophical, psychological, and pedagogical theories underpinning investigative thinking and examines how integrative and creative principles can be systematically employed to enhance students’ intellectual autonomy and research-oriented competencies. Drawing on contemporary educational theory and empirical research, the article highlights the potential of integrative-creative pedagogy to foster deep learning, cognitive flexibility, and sustained intellectual engagement. The findings contribute to the theoretical substantiation of innovative educational practices and offer a conceptual framework for educators seeking to cultivate investigative thinking in diverse learning environments.